All aboard! Insights from remote pilot operators informing maritime operations - Aguiar, B.; Rosa, M.; Pinto, M. (IDEIA 2022 - Space relevance for Maritime Operations and Blue Economy, 2022)
Unmanned Automated Vehicles (UAVs) have entered our sky, and in a near future, it is expected that we will live in a U-Space where mixed traffic operates, and space is explored resorting to UAVs. This is only possible due to the technological disruption of Industry 4.0, and the consequential implementation of more complex automated systems. Automation is permeating other sectors, such as the maritime, with consequences for human-machine interface, which, if not addressed, may negatively impact the workforce and the market. Recent data from the EU funded project “Skill-UP” (2021) regarding UAVs show that the success of these transitions relies on training and skilling the workforce - remote pilot operators (RPAs). Both survey and interview data showed that behavioral skills training was deemed essential to the adaptation to the future work scenario. RPAs interviewed – which included employees, trainers, and employers – pointed out the importance of skills such as decision making, teamwork/collaboration, and emotion management. RPA’s will be more accountable for monitoring and intervene in complex and/or unpredictable situations, which will require fast and accurate decision-making. These are important lessons to be transferred to the maritime sector as well, not only because they share similar challenges and demands, but also because the maritime, defense and aerospace sectors need to work in synergy. Therefore, in line with the EU Pact for Skills in industry, we bring forward the idea to replicate and adapt this framework to RPAs in the maritime sector, in synergy with advances in space UAVs. Innovation that considers multiple angles (e.g. technological, human) will be more impactful than a purely technological approach, while providing important insights for managing the human side of technological disruption.